Салихат: [роман] / Наталья Елецкая - Елецкая Наталья Владимировна (Это личное!, 2022)
Экземпляры: с/ф № 8 (20231013) / Инвентарный номер: 51484 / Цена: / Авт.знак: Е 50 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44